Impact of the sensory experience on consumers’ preference toward the origin of honey: a case study in Mar del Plata, Argentina - Kallas, Zein (2017)
This study analysed consumers' expected preference toward local honey with different colour and texture. We analysed the impact of the sensory experience on consumers' expectation and their willingness to pay for the honey products. We carried out two Non-Hypothetical Discrete Choice Experiments (DCE) by creating a real shopping scenario before and after the hedonic sensory test for a sample of 145 consumers from Mar del Plata, Argentina. Data used in this analysis were obtained from questionnaires completed in a controlled environment and estimated using the random parameters Logit model (MIXL). Results showed both high preference and acceptance for local honey with solid texture and light colour and also revealed a high rejection for dark honeys. Consumers also declared their willingness to pay a premium for their most preferred honey type if it is produced from local place. The sensory experience has had impact on expectation. Consumers were not willing to compromise their perceived quality and their eating experience with other descriptors of the honey product.